Epidemiology of liver cancer in Kazakhstan: data from the Unified National Electronic Health System, 2014–2023 - Ayana Ablayeva; Dmitriy Syssoyev; Ruslan Akhmedullin; Altynay Beyembetova; Diyora Abdukhakimova; Temirgali Aimyshev; Iliyar Arupzhanov; Gulnur Zhakhina; Aigerim Biniyazova; Temirlan Seyil; Nurbek Igissin; Yuliya Semenova; et al. (PLoS ONE, 2025)
Background Liver cancer is the third-deadliest cancer globally, significantly affecting the Asian population, which accounts for 70% of cases. Despite these numbers, the burden of liver cancer in Central Asia, including Kazakhstan, remains underexplored. This paper reviews the epidemiology of liver cancer in Kazakhstan by analyzing large-scale administrative data from the national registry. Methods The study cohort included 10,455 patients diagnosed with liver neoplasms (C22.0-C22.9, D13.4) from 2014 to 2023, using the International Classification of Diseases, 10th Revision (ICD-10). Age-standardized incidence, mortality, and prevalence rates per 100,000 population were calculated. Cox regression analysis estimated hazard ratios across social-demographic and medical predictors. Results Over the decade, age-standardized incidence rates decreased from 5.55 to 5.40 per 100,000, while mortality rates rose from 3.75 to 4.75 per 100,000. A downward trend appeared between 2017–2019 but gradually reversed post-2020. Prevalence rates steadily increased from 1.30 to 7.32 per 100,000. The cohort’s mean age was 63.2 ± 0.1 years, with most cases diagnosed as stage III hepatocellular carcinoma. West Kazakhstan, East Kazakhstan, and Pavlodar were the most burdened regions. Liver cirrhosis history predicted worse survival (Hazard Ratio, HR = 1.14; 95% CI 1.06–1.22), while primary hypertension showed a protective effect (HR = 0.82; 95% CI 0.78–0.86). Conclusions Liver cancer morbidity and mortality rates have risen in Kazakhstan over the past decade, with a slight decrease during the early COVID-19 pandemic. Patients are mostly diagnosed with stage III hepatocellular carcinoma. West Kazakhstan, East Kazakhstan, and Pavlodar are the most affected regions, requiring better management of high-risk groups. Poor survival was linked to liver cirrhosis. Further research on the role of rising metabolic liver diseases and treatment options in Kazakhstan is needed to better predict liver cancer prognosis.